Anti-hiperglycemic effect of Quassia amara (Simaroubaceae) in normal and diabetic rats - S.F. Ferreira; S.C.S.F. Azevedo; M. Vardanega-Peicher; C.L.S. Pagadigorria; R.F. Garcia (Universidade Estadual Paulista, 2013)
The anti-hyperglycemic effect of wood powder of Quassia amara (QA) was evaluated in normal and in alloxan diabetes-induced rats. After a 12 h fast and glycemic check, the animals were orally given 0.9% of saline (control group), metformin (500 mg/kg) or QA (200 mg/kg) and, 30 minutes later, they received an oral glucose dose (1g/kg). The blood glucose level was measured after 30, 60, 90 and 120 minutes. From the oral glucose dose, QA showed anti-hyperglycemic effects, similar to metformin, only in the diabetic animals (p<0.01) when compared to the control group. Although the anti-hyperglycemic mechanism of action of QA was not investigated, a mechanism similar to metformin can be suggested, since both presented similar results for the conditions tested, that is, normal and diabetic rats. It is believed that the use of QA in diabetics could help to control the blood glucose levels and be useful as an alternative therapy.